2006
DOI: 10.1190/1.2187795
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelasticity of precompacted unconsolidated sand with viscous cement

Abstract: The elastic properties of sand strongly depend on the grains' contact stiffness, which can be increased significantly by solid matter and, depending on frequency, viscous fluid acting as contact cement. To calculate seismic velocities in precompacted fluid-cemented sand, we examine how a small amount of viscous fluid at the grain contacts influences their normal and tangential stiffnesses as a function of effective pressure. Using the Hertz-Mindlin approach and considering oscillatory loading in addition to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…() showed that the presence of pores with a low aspect ratio leads to a dramatic increase of the difference between effective shear moduli of the dry and solid saturated rock, an effect similar to the stiffening effect of squirt flow in fluid‐filled rocks at ultrasonic frequencies. This similarity was recognized by Leurer and Dvorkin () who proposed the term ‘solid squirt’ to describe the stiffening of the compliant grain contacts by a solid infill. More generally, the works of Leurer and Dvorkin () and Makarynska et al .…”
Section: Introductionmentioning
confidence: 70%
“…() showed that the presence of pores with a low aspect ratio leads to a dramatic increase of the difference between effective shear moduli of the dry and solid saturated rock, an effect similar to the stiffening effect of squirt flow in fluid‐filled rocks at ultrasonic frequencies. This similarity was recognized by Leurer and Dvorkin () who proposed the term ‘solid squirt’ to describe the stiffening of the compliant grain contacts by a solid infill. More generally, the works of Leurer and Dvorkin () and Makarynska et al .…”
Section: Introductionmentioning
confidence: 70%
“…Rather than modifying the BSM, the original Biot formulation is used as the general framework. Two viscoelastic models are included that consist of extended formulations of ͑1͒ an effectivegrain model 15 ͑EGM͒ and ͑2͒ a viscoelastic-contact model 24 ͑VCM͒. Nevertheless, it can still be argued that the model presented here, apart from the EGM, represents a refinement of the BSM, because it was the original idea of introducing an energy-dissipating skeletal frame that made Biot's theory applicable to unconsolidated marine sediment.…”
Section: Introductionmentioning
confidence: 96%
“…The Cole-Cole model describes well the frequency dependencies of velocities and absorptions in the frequency range from units of hertz to hundreds of kilohertz (Batzle et al, 2006;Gurevich et al, 2008;Jones, 1986;. In the works of Leurer and Dvorkin (2000); Leurer and Dvorkin (2006) the Cole-Cole method has been successfully applied for the description of squirt flows in granular geomaterials whose grains are covered with viscous fluid.…”
Section: Introductionmentioning
confidence: 98%